'IT IS IMPORTANT ARTISTS REACT TO THE WORLD IN WHICH WE ALL LIVE': AN INTERVIEW WITH PHILIPPE MANOURY ON LAB.ORATORIUM. (July 2020) - Velasco-Pufleau, Luis; Manoury, Philippe
Abstract: Lab.Oratorium (2019) is the concluding part of Philippe Manoury's Köln Trilogy . It follows In situ (2013) and Ring (2016) in exploring the spoken voice as a musical element, the wider possibilities of the orchestra, and the use of sound spatialization and live electronics. Lab.Oratorium is also a work deeply rooted in the present. In this interview, Philippe Manoury discusses the political and poetic significance of this work, conceived as an artistic response to Europe's responsibility in the tragic situation of migrants around the Mediterranean. He also develops his thoughts on musical form, spatialization and creative process in music.